Tantangan Pendidikan Islam Di Era Globalisasi Dan Perdagangan Bebas - Dede Misbahul Alam; Nasrullah; R. Nursuhada (STKIP Subang, 2026)
Globalization and free trade have brought significant changes to various aspects of life, including education. Islamic education, as an educational system based on Islamic values, faces various serious challenges amidst the currents of globalization characterized by technological advances, economic liberalization, and cross-border cultural exchange. This study aims to analyze the main challenges of Islamic education in the era of globalization and free trade and the strategic efforts that can be made to address them. The research method used is qualitative research with a library research approach, by reviewing various literature in the form of books, scientific journals, and other relevant documents. The results show that the challenges of Islamic education include global competition for the quality of human resources and Islamic education, the response of Islamic education to the development of modern technology, the impact of moral decadence on students, materialistic orientations affecting the goals of Islamic education, and the threat of brain drain. Therefore, Islamic education is required to innovate its curriculum, strengthen character, improve the professionalism of educators, and utilize digital technology wisely to remain relevant and competitive without losing its Islamic identity.